1960
DOI: 10.1139/o60-119
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Action of Tocopherol Against Hemolysis of Rat Erythrocytes by Dialuric Acid

Abstract: Erythrocytes from rats on tocopherol-deficient and tocopherol-supplemented diets gave similar low values for lipid peroxides by the thiobarbituric acid test. Treatment of the cells from tocopherol-deficient rats with dialuric acid caused a marked increase in lipid peroxitles and this closely paralleled the degree of hernolysis. Shaking of the red cells from tocopherol-deficient arlimals in a n atmosphere of oxygen also resulted in a slow lipid peroxidatio~l which again paralleled the degree of hernolysis. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1966
1966
1992
1992

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Work in other laboratories and our own studies had linked high oxygen tensions, erythrocyte lysis, and lipid peroxidation in vitro (11)(12)(13)(14)(15)(16)(17), and previous studies in this laboratory had suggested their relationship in vivo (21)(22)(23). The present studies establish the fact that peroxidation of erythrocyte lipid can occur in vivo during exposure to oxygen under high pressure.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…Work in other laboratories and our own studies had linked high oxygen tensions, erythrocyte lysis, and lipid peroxidation in vitro (11)(12)(13)(14)(15)(16)(17), and previous studies in this laboratory had suggested their relationship in vivo (21)(22)(23). The present studies establish the fact that peroxidation of erythrocyte lipid can occur in vivo during exposure to oxygen under high pressure.…”
Section: Methodssupporting
confidence: 80%
“…Since no tocopherol assays were performed on erythrocytes, plasma, or other tissues of these mice, the question of their tocopherol status merits comment. Excellent evidence of their tocopherol deficiency was provided by the accentuated lysis and lipid peroxidation of their erythrocytes by hydrogen peroxide, as compared to normal mouse erythrocytes (11,13,14,19). Whereas susceptibility to lipid peroxidation can be increased by diet-induced alterations in composition of erythrocyte lipid, specifically by an increase in erythrocyte unsaturated fatty acid content, this was unlikely in these experiments since the diet contained 10%o lard rather than unsaturated fatty acids.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The possibility of a comparable lipid alteration occur-experimental animals (3,4,7,9,10) and man (5,11,12). Recently, Kayden and Silber reported that patients with abetalipoproteinemia (acanthocytosis) were deficient in vitamin E; in fact, the serum tocopherol levels were the lowest reported for man (13).…”
Section: Introductionmentioning
confidence: 99%
“…The association of the oxidative breakdown of cell membrane UFA with hemolysis has been noted in studies of normal and vitamin E-deficient erythrocytes exposed to oxidizing agents (30,(50)(51)(52). Mengel and his coworkers, in a series of investigations evaluating the hemolytic effects of hyperbaric oxygenation, demonstrated that lipid peroxidation preceded hemolysis both in vitro and in vivo (53,54).…”
Section: Discussionmentioning
confidence: 99%